Association of IL-9, IL-10, and IL-17 Cytokines With Hepatic Fibrosis in Human Schistosoma mansoni Infection - Franco, Karine Garcez Schuster; de Amorim, Fabio Jorge Ramalho; Santos, Mário Adriano; Rollemberg, Carla Virgínia Vieira; de Oliveira, Fabricia Alvisi; França, Alex Vianey Callado; Santos, Camilla Natália Oliveira; Magalhães, Lucas Sousa; Cazzaniga, Rodrigo Anselmo; de Lima, Frederico Santana; Benevides, Luciana; Carregaro, Vanessa; et al. (Frontiers in Immunology, 2021)
This is a case series study to evaluate immunological markers associated with schistosomiasis advanced fibrosis, including 69 patients from an endemic area from the State of Sergipe, and from the Hepatology Service of the University Hospital in Sergipe, Brazil. Hepatic fibrosis was classified based on Niamey protocol for ultrasonography (US). Immune response to Schistosoma mansoni antigens was evaluated by stimulating peripheral blood mononuclear cells (PBMC) from these patients with either adult worm (SWAP-10μg/mL) or egg (SEA-10 μg/mL) antigens, or purified protein derivative of turberculin (PPD-10 μg/mL) or phytohemagglutinin (PHA-1μg/mL) for 72 hours. The levels of IFN-γ, TNF-α, IL-5, IL-10, IL-17 were measured in these supernatants by ELISA and IL-9 by Luminex. Single nucleotide polymorphism in IL-17, IL10 and CD209 genes were genotyped using TaqMan probe by qPCR. Higher levels of IL-9, IL-10 and IL-17 were found in PBMC supernatants of patients with advanced hepatic fibrosis. Direct correlations were detected between IL-9 and IL-17 levels with US spleen sizes, portal vein diameters and periportal thickening. The CD209 rs2287886 AG polymorphism patients produce higher IL-17 levels. Together, these data suggest a role of these cytokines in the immunopathogenesis of advanced fibrosis in human schistosomiasis.